Pembekalan Pembuatan CV kepada Siswa SMA Plus Assa’adah Sebagai Modal Dalam Memasuki Dunia Kerja - Sumardi Sumardi; Edi Setiawan; Zulpahmi Zulpahmi; Kilah Nurjanah; Adelia Sari (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Community service activities are social activities aimed at the community as one of the chess dharma of higher education. In order to achieve the chess dharma of higher education, FEB UHAMKA lecturers carry out community service activities for SMA Plus Assa'adah students. This activity is intended so that students have a deep understanding of preparing a curriculum vitae (CV) so that they have a basis for entering the world of work. The activity was carried out using the lecture method, this method was chosen so that the delivery of material could run effectively. Participants who attended the implementation of this activity were 129 students of SMA Plus Assa'adah. Participants were given the opportunity to ask the speaker, so that things that were not understood could be answered optimally.